4-(5-7x)=2(x+1)

Simple and best practice solution for 4-(5-7x)=2(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-(5-7x)=2(x+1) equation:


Simplifying
4 + -1(5 + -7x) = 2(x + 1)
4 + (5 * -1 + -7x * -1) = 2(x + 1)
4 + (-5 + 7x) = 2(x + 1)

Combine like terms: 4 + -5 = -1
-1 + 7x = 2(x + 1)

Reorder the terms:
-1 + 7x = 2(1 + x)
-1 + 7x = (1 * 2 + x * 2)
-1 + 7x = (2 + 2x)

Solving
-1 + 7x = 2 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-1 + 7x + -2x = 2 + 2x + -2x

Combine like terms: 7x + -2x = 5x
-1 + 5x = 2 + 2x + -2x

Combine like terms: 2x + -2x = 0
-1 + 5x = 2 + 0
-1 + 5x = 2

Add '1' to each side of the equation.
-1 + 1 + 5x = 2 + 1

Combine like terms: -1 + 1 = 0
0 + 5x = 2 + 1
5x = 2 + 1

Combine like terms: 2 + 1 = 3
5x = 3

Divide each side by '5'.
x = 0.6

Simplifying
x = 0.6

See similar equations:

| M-27=-46 | | (2a+3b+4c)+(4a+2b)= | | 2u=10 | | 7=t+6 | | 7 = t + 6 | | X(x-4)(x+7)(2x-9)=0 | | 9x=-8y+72 | | 3(7+x)=24 | | 7x+5=21 | | 3x^3-24x^2+36x=0 | | 11k-8k-3=9 | | -x+7=8 | | (2x+3)(x-5)=2(x^2-6x+5) | | 3t+8(2t-6)+2=14t | | Y^2+2y-120=0 | | y=2.6 | | 7k-8-2(k-12)=52 | | 10+x^2-7x=0 | | a^2=24-10a | | 1/2=12+18 | | 2x^3-44x^2+240x=0 | | 8x+9+3=6 | | -4x^2(3x-7)=0 | | r^2-11r=-18 | | 10=0.1x^2+4x | | (4+z)=-1 | | (x+3)=5 | | c(210)= | | (12n-4)/2=1-10n | | 9-c=13 | | 4m=-8 | | 3(x+1)+1=3x+4 |

Equations solver categories